2012
DOI: 10.1109/jsen.2011.2111453
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Simplified Adaptive Noise Cancelers for ECG Sensor Based Remote Health Monitoring

Abstract: In this paper, several simple and efficient sign and error nonlinearity-based adaptive filters, which are computationally superior having multiplier free weight update loops are used for cancellation of noise in electrocardiographic (ECG) signals. The proposed implementation is suitable for applications such as biotelemetry, where large signal to noise ratios with less computational complexity are required. These schemes mostly employ simple addition, shift operations and achieve considerable speed up over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…But it is especially reasonable for applications requiring substantial signal to noise proportions with less computational complexity [14]. Similarly, many trials have been made to cancel the noise from ECG signal with modification of existing algorithms [14][15][16][17][18][19][20][21]. But the literature cannot provide sufficient information regarding impulsive noise cancellation from cardiac signal.…”
Section: Related Literaturementioning
confidence: 99%
“…But it is especially reasonable for applications requiring substantial signal to noise proportions with less computational complexity [14]. Similarly, many trials have been made to cancel the noise from ECG signal with modification of existing algorithms [14][15][16][17][18][19][20][21]. But the literature cannot provide sufficient information regarding impulsive noise cancellation from cardiac signal.…”
Section: Related Literaturementioning
confidence: 99%
“…There are different techniques available for use in denoising ECG signals, such as wavelet, [4][5][6][7][8][9] adaptive filtering, [11][12][13][14] empirical mode decomposition (EMD) 15 16 and more.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14]. Rahman, et al 15 proposed several adaptive recurrent filters, such assigned regressor algorithm (SRA), normalized least mean square (NLMS), and error nonlinear confirmed that the performance of sign-based algorithms is better than the LMS counterpart. Adaptive filters often require noise reference signals, which are difficult to obtain with the ECG signal acquisition system as an input.…”
Section: Introductionmentioning
confidence: 99%
“…This means that lesser time will be available to carry out the computations of filtering operation. 23,24 Thus far, to the best of the authors knowledge, no effort has been made to reduce the computational complexity of the ANC in the context of brain signal enhancement. A typical Least Mean Square (LMS) based ANC has a drawback of estimating the coefficients of linear expansion.…”
Section: Introductionmentioning
confidence: 99%